Multifaced roles of PLAC8 in cancer - Misha Mao; Yifan Cheng; Jingjing Yang; Yongxia Chen; Ling Xu; Xun Zhang; Zhaoqing Li; Cong Chen; Siwei Ju; Jichun Zhou; Linbo Wang (BMC, 2021)
Abstract The role of PLAC8 in tumorigenesis has been gradually elucidated with the development of research. Although there are common molecular mechanisms that enforce cell growth, the impact of PLAC8 is varied and can, in some instances, have opposite effects on tumorigenesis. To systematically understand the role of PLAC8 in tumors, the molecular functions of PLAC8 in cancer will be discussed by focusing on how PLAC8 impacts tumorigenesis when it arises within tumor cells and how these roles can change in different stages of cancer progression with the ultimate goal of suppressing PLAC8-relevant cancer behavior and related pathologies. In addition, we highlight the diversity of PLAC8 in different tumors and its functional output beyond cancer cell growth. The comprehension of PLAC8's molecular function might provide new target and lead to the development of novel anticancer therapies.